Visualização em multirresolução do fluxo de tópicos em coleções de texto - Schneider, Bruno (2014)
The combined use of algorithms for topic discovery in document collections with topic flow visualization techniques allows the exploration of thematic patterns in long corpus. In this task, those patterns could be revealed through compact visual representations. This research has investigated the requirements for viewing data about the thematic composition of documents obtained through topic modeling - where datasets are sparse and has multi-attributes - at different levels of detail through the development of an own technique and the use of an open source library for data visualization, comparatively. About the studied problem of topic flow visualization, we observed the presence of conflicting requirements for data display in different resolutions, which led to detailed investigation on ways of manipulating and displaying this data. In this study, the hypothesis put forward was that the integrated use of more than one visualization technique according to the resolution of data expands the possibilities for exploitation of the object under study in relation to what would be obtained using only one method. The exhibition of the limits on the use of these techniques according to the resolution of data exploration is the main contribution of this work, in order to provide subsidies for the development of new applications.